2012
DOI: 10.1016/s1348-8643(12)00009-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of the biological function of the osteocytic lacunar canalicular system and of osteocyte‐derived factors

Abstract: Osteocytes are organized in functional syncytia collectively referred to as the osteocytic lacunar‐canalicular system (OLCS). The osteocytes are interconnected through gap junctions between their cytoplasmic processes, which pass through narrow passageways referred to as osteocytic canaliculi. There are two possible ways molecules can be transported throughout the OLCS: via the cytoplasmic processes and their gap junctions, and via the pericellular space in the osteocytic canaliculi. Transport of minerals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…5 and 6, we could hypothesize that osteoblasts seem to be able to "stock" their cytoplasmic processes on the osteoid in the primary trabeculae, which is marked by a high bone formation rate (17,18). We have previously demonstrated the distribution of osteocytes and their cytoplasmic processes were irregularly-arranged in the immature primary trabeculae, though they were regular in the mature cortical bone (14)(15)(16). It may be reasonable that osteoblasts' cytoplasmic processes also irregularly-oriented and accumulated in the osteoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6, we could hypothesize that osteoblasts seem to be able to "stock" their cytoplasmic processes on the osteoid in the primary trabeculae, which is marked by a high bone formation rate (17,18). We have previously demonstrated the distribution of osteocytes and their cytoplasmic processes were irregularly-arranged in the immature primary trabeculae, though they were regular in the mature cortical bone (14)(15)(16). It may be reasonable that osteoblasts' cytoplasmic processes also irregularly-oriented and accumulated in the osteoid.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of normal endochondral ossification (8,13), osteoblasts extend their cytoplasmic processes into the bone matrix of the primary trabeculae (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Cortical bone is a mature, well-mineralized hard tissue that composes the outer wall of the long bone. OLCS distribution differs depending on such regional difference of bone (13,31,37). Immature, primary trabeculae contained randomly-oriented OLCS, revealing an intense tissue nonspecific alkaline phosphatase (TNAP)-reactivity, a hallmark of osteoblastic activities (3,26), on their surface.…”
Section: Methodsmentioning
confidence: 99%
“…Osteocytes exist inside osteocytic lacunae and connect to neighboring osteocytes and osteoblasts on the bone surfaces via fine cytoplasmic processes that run through osteocytic canaliculi. Osteocytes interconnect their cytoplasmic processes via gap junctions (2,6,7,33), thereby building functional syncytia referred to as osteocytic lacunar-canalicular system (OLCS) (5,15,16,31).…”
Section: Introductionmentioning
confidence: 99%
“…26) As the osteocyte networks display a regular geometry in lamellar bone and osteocytes align parallel to the lamellar plane and elongate canaliculi mainly perpendicular to the lamellar plane, 27,28) some studies have suggested that the arrangement of the osteocyte networks is crucial for the efcient monitoring of mechanical strain and transportation of molecules. 29,30) Therefore, studying the correlative geometry of vascular networks and osteocyte networks may be helpful to further understanding of bone function as a mechanosensitive and endocrine system.…”
Section: )mentioning
confidence: 99%